Improving geotechnical properties using paper ash and olive pomace - Inas Berdi; Salah Messast; Riad Benzaid; Imane Idoui (Selected Scientific Papers: Journal of Civil Engineering)
Soil stabilization techniques play a crucial role in improving soil quality, reducing construction costs, and addressing environmental and mechanical challenges encountered in civil engineering. Faced with low-quality soils, several researchers have explored innovative solutions by using natural waste materials. New approaches are being developed to recover local waste and reuse it in civil engineering applications, particularly in earthworks. In this study, the goal is to experimentally compare the impact of two types of waste on the stabilization of clay soils, by testing different percentages (2%, 4%, 6%, 8%) through various laboratory tests, such as compressive strength, shear strength, and oedometer compression test. The results obtained are analyzed to evaluate the effectiveness of these wastes in soil treatment. The preliminary study conducted on the clay soil showed a significant improvement in its mechanical properties, which could enhance its stability and bearing capacity.